The Relationship of Iron Metabolism and Hepcidin in Childhood - Semercioğlu, Elif Almıla; Solgun, Hüseyin Avni; Kılınç, Yurdanur (Cerrahpaşa Medical Journal, 2020)
Objective: In this study, we aimed to evaluate the hemoglobin, hematocrit, mean erythrocyte volume, iron binding capacity, ferritin, transferrin saturation index, and hepcidin levels in children with and without iron deficiency anemia, and to determine the difference or relationship between hepcidin values in these two groups. Methods: Childeren those who are between the ages of 1 to 16 and have applied to the Çukurova University Faculty of Medicine Pediatrics outpatient clinic; A total of 94 patients who were diagnosed with iron deficiency anemia according to their iron, iron binding capacity and serum ferritin values, with transferrin saturation <16% and normal C-Reactive protein, and childeren also aged between 1 to 16; 91 healthy children with normal hemoglobin electrophoresis were included in the study. Blood samples were taken for complete blood count, serum iron, iron binding capacity, ferritin, C-reactive protein, and hepcidin parameters of the two groups. Results: When the results were evaluated, the mean serum hepcidin levels were 219.51±70.72 ng/mL in the control group and 141.44±71.53 ng/mL in the patient group. The difference between the mean values of the two groups was statistically significant (p<0.05). There was no statistically significant correlation between serum hepcidin levels and serum hemoglobin, iron and ferritin levels in both patient and control groups. Conclusion: Hepcidin may play a critical role in diagnosis and treatment of iron metabolism diseases, and in literature, more studies are needed to clarify this role. Cite this article as: Semercioğlu EA, Solgun HA, Kılıç Y. The Relationship of Iron Metabolism and Hepcidin in Childhood. Cerrahpaşa Med J 2020; 44(3): 145-152.